Gold-catalyzed 1,n-enyne cycloisomerizations as synthetic strategies to nitrogen heterocycles - Huang, Chuhui (2012)
The work in this thesis was undertaken in Chemistry and Biological Chemistry, School of Physical and Mathematical Sciences in Nanyang Technological University from January 2010 to December 2011 under the supervision of Asst Prof Philip Wai Hong Chan. The work of this thesis has been directed toward the efficient synthesis of 1,7-enyne and its application towards nitrogen heterocycles synthesis via gold-catalyzed 1,7-enyne cycloisomerization. This thesis is divided into four chapters: